Ternary composite phase change materials (PCMs) towards low phase separation and supercooling: eutectic behaviors and application. (November 2022) - Xing, Xianghai; Lu, Wei; Zhang, Guanhua; Wu, Yupeng; Du, Yanping; Xiong, Zhibo; Wang, Li; Du, Kun; Wang, Hao
Abstract: Salt hydrates have been used as phase change materials (PCMs) for various types of Thermal Energy Storage (TES) especially for cold storage. In this project, a novel composite phase change material (PCM) consisted of mixed solution of inorganic salt and organic salt was developed and characterized. Firstly, the PCM solutions containing sodium formate, potassium chloride and water with various weight percentage were evaluated to understand their solidification temperature, melting temperature, the supercooling degree and the latent heat. Then a PCM with mass fractions at weight percentages of 22%/12%/66% with better performance was selected for further study to restrain the supercooling. Different gelling agents and nucleate agents were employed in this PCM. The results show that the addition of 0.6 wt% xanthan gum can effectively prevent the phase separation and leakage, while 0.6 wt% of nano-TiO2 is the best nucleating agent since the supercooling can be reduced to 2.6 °C, which is 67.9% lower than that of the original PCM without any nucleating agent. Finally, the novel PCM was tested for frozen food storage application, in which the food temperature could be maintained below -18 °C for over 10 hours in the insulated box. This indicated the suitability of developed PCM for frozen food storage and transportation.